Optimization of Standalone Photovoltaic System Considering Loss of Power Supply Probability for Repeater Station of Nepal Telecom - Ranjit, Krishna; Maharjan, Sanjeev (Journal of Advanced College of Engineering and Management, 2019)
Telecommunication plays the vital role in the human life and has become an integrated part of the society. The rapidly growing information and communications technology and increasing competition in telecommunication markets triggers the telecom operators to extend their networks and services to their potential customers in different geographical locations. It necessitates them to install repeaters and communication towers powered by standalone Photovoltaic system in remote rural areas. This paper presents optimization of standalone photovoltaic system maximizing reliability in one of such remotely located Palethar Repeater Station of Nepal Telecom situated in Dadeldhura district of Far-western region. The optimization is carried out using Genetic Algorithm in MATLAB software for given load profile enhancing reliability of the system with maximum reduction of overall system cost. The loss of power supply probability (LPSP) is considered for reflecting the reliability of the system. The paper discusses different optimal configuration of standalone PV system under various values of LPSP after optimization.